The Use of Cooperative Principle in Students’ Conversation - Togatorop, Firinta (Journal of Applied Linguistics, 2024)
This research explored the application of Grice's Cooperative Principle in the conversations of eighth-grade students at SMP N I Pematangsiantar. The study aimed to identify the types of cooperative principles employed by students and determine the most dominant one. Drawing on Grice (1975) and Levinson's (1983) theories, the four types of cooperative principles examined are the Maxim of Quality, the Maxim of Quantity, the Maxim of Manner, and the Maxim of Relevance. This study employed a descriptive qualitative research method, the data consisted of 30 conversations, revealing that students predominantly utilize all four types of cooperative principles. However, the most dominant principle is the Maxim of Quantity, accounting for 34.17%, followed by the Maxim of Relevance (30.37%), the Maxim of Manner (22.78%), and the Maxim of Quality (12.65%). The findings suggested that cooperative principles play a crucial role in enhancing communication and facilitating comfortable and easily understandable conversations among students. As a conclusion, this research underscores the significance of cooperative principles in conversational dynamics, recommending further study for linguistic students to deepen their understanding of these principles. Keywords : Linguistics, Cooperative principle, Maxim